Hubungan Kehamilan Remaja, Pemberian MP-ASI dan Riwayat Imunisasi Terhadap Kejadian Stunting Pada Baduta Usia 6-24 Bulan di Wilayah Puskesmas Bojongsari - Suci Permatasary, (2020)
Stunting is one of several nutritional problems that occur in children. The prevalence of stunting in Indonesia still shows a high number and is a result of the high number of factors that affect such as; adolescent's pregnancy, error in complementary feeding of the breastfed and incomplete history of immunization. The purpose of this research was to analyze the relationship between adolescent pregnancy, complementary feeding of the breastfed and immunization history against the incidence of stunting in infants aged 6-24 months. The type of this research was quantitative research with cross-sectional study design. A total of 49 respondents were selected by multiple stages sampling method. Data was collected from online questionnaire and the data length of the body using measurement data of cadres. The data were analyze using univariate analysis, bivariate analysis with chi-square and fisher's exact test and multivariate analysis with multiple logistic regression test. The result of this research showed that were relationship between adolescent pregnancy (p=0,039) and complementary feeding of the breastfed (p=0,010) with the incidence of stunting and the adolescent pregnancy had the most dominant relationship with odds ratio of 6,444.